Reflecting Inclusivity: Disability Narratives in Indonesian Children’s Literature - Kusuma Dewi, Silfiyah Indriyati; Ramadhani, Andi Reski; Kitri, Ainul (POETIKA, 2025)
Disability representation often perpetuates harmful stigmatization and stereotyping. This study examines disability narratives in the Indonesian children’s book Kumpulan Cerita Anak Istimewa: Aku Memang Beda (Collection of Special Children’s Stories: I Am Different) by Erna Fitrini and Ratih Soe. Given the complexity and diversity of disabled persons’ experiences, this study cannot provide a comprehensive account of all representational forms. This research employs a mixed descriptive-qualitative and quantitative methodology using reading and note-taking techniques. The quantitative approach identified various disability narrative forms within the children’s book, while grouping and analysis yielded 63 data points. These data were analyzed through Mitchell and Snyder’s narrative prosthesis theory. While narrative prosthesis theory has primarily been applied within Western adult literary studies, extending this theoretical framework to Indonesian children’s literature represents a significant scholarly innovation, offering critical insights into disability’s narrative construction and representation within localized cultural and literary contexts. Analysis reveals that disability frequently serves as a characterization tool, symbol, object of perspective, and plot device. The findings show that existing narratives emphasize physical and mental differences, potentially limiting understanding of people with disabilities as complete individuals. Additionally, character complexity is often overlooked when disability functions as a plot mechanism. This study advocates for more inclusive approaches to disability representation in children’s literature to prevent reinforcing stereotypes and stigma against people with disabilities.